2019
DOI: 10.17263/jlls.547730
|View full text |Cite
|
Sign up to set email alerts
|

EFL students’ vocabulary learning strategies and their affixes knowledge

Abstract: Vocabulary Learning Strategies and knowledge of affixes have long been considered to have influence on learners' vocabulary learning. However, how they relate to each other seems to have drawn little attention. This current study was intended to explore the frequency of vocabulary learning strategies used by Indonesian high school students, to find out their knowledge of affixes as well as to figure out how their reported vocabulary learning strategies use relate to their knowledge of affixes. This correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…One interesting finding which came Arab World English Journal www.awej.org ISSN: 2229-9327 163 to light through the present study was the significant role of analyzing the context where an unknown word occurred in terms of the structure of the word itself, and its grammatical class. These sub-strategies when put together under Strategy One were implemented more than the rest of the VDSs by the participants of the study, and this is consistent with the findings of most of the studies reviewed in the literature part such as Anderson, (2005), Baumann, Kame'enui, & Ash, (2003), Borer (2007), Ellis (1995), Memiş (2018), Schmitt & McCarthy (1997), Nopriato and Purnawarman (2019), and Nyikos & Fan (2007). This is a clear indication that guessing the meaning of a word from context requires performing higher levels of cognitive processes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…One interesting finding which came Arab World English Journal www.awej.org ISSN: 2229-9327 163 to light through the present study was the significant role of analyzing the context where an unknown word occurred in terms of the structure of the word itself, and its grammatical class. These sub-strategies when put together under Strategy One were implemented more than the rest of the VDSs by the participants of the study, and this is consistent with the findings of most of the studies reviewed in the literature part such as Anderson, (2005), Baumann, Kame'enui, & Ash, (2003), Borer (2007), Ellis (1995), Memiş (2018), Schmitt & McCarthy (1997), Nopriato and Purnawarman (2019), and Nyikos & Fan (2007). This is a clear indication that guessing the meaning of a word from context requires performing higher levels of cognitive processes.…”
Section: Discussionsupporting
confidence: 84%
“…Schmitt's argument was supported by Nyikos and Fan (2007), and Anderson (2005) who too observed that such L2 learners succeed in vocabulary learning who select more complex and taskcompatible strategies for learning new L2 words. In this regard, a very good example was cited by Nopriato and Purnawarman (2019) who studied the level of implementation of VLSs of Indonesian L2 learners and concluded that Indonesian learners showed moderate use of VLS with more emphasis on the determination category of VLSs. Memiş 2018, in a recent study, also reached a similar conclusion who reported that strategies used by L2 learners varied according to their language level.…”
Section: Research Questionsmentioning
confidence: 99%
“…There have been various studies on strategies, techniques, or approaches used in teaching/learning English vocabulary such as usage of keywords: correlating the L2 word with an L1 keyword which is acoustically or orthographically alike, and by doing so, linking the L1 keyword with the L1 translation of the L2 word (Brown & Perry, 1991), semantic and thematic clustering (Tinkham, 1997), role of pedagogical tasks and form-focused instruction (De la Fuente, 2006), usage of word pairs (Webb, 2009), reading thematically related texts (Paribakht & Wesche, 1999), incidental vocabulary learning (Wode, 1999), intentional vocabulary learning (Brown, 2010), rote rehearsal vs. context/keyword methods (Rodriguez & Sadoski, 2000), input-based and production-based instruction (Shintani, 2011), use of categorical lists (Hoshino, 2010), explicit instruction of vocabulary (Mizumoto & Takeuchi, 2009), code-mixing: the use of L1 word in an L2 utterance (Celik, 2003), semantic transfer (Jiang, 2004), focus on Knowledge of affixes and morphological awareness (Noprianto & Purnawarman, 2019;Sarfraz, Tariq, & Abbas, 2018), spontaneous vocabulary reactivation (Meara, 2005), rote memorization, that is to memorize the L1 translation of a new L2 term; as opposed to semantic mapping that is to www.scholink.org/ojs/index.php/selt Studies in English Language Teaching Vol. 8, No.…”
Section: Which Method/technique To Choose?mentioning
confidence: 99%
“…In English language learning process, interaction and communication between the students and their environment is necessitated because it an imperative element to embody the language (Studies, 2017). As English language learner may know that the fundamental of learning a language is to use it as tool both in spoken and in written for the purpose of communication (Noprianto & Purnawarman, 2019) Therefore it is important for the English teachers to provide directed teaching instructions to help students to enhance their vocabulary knowledge so that they will be able use the language (Subon, 2016). As a matter of fact, the ability to use English language will not gradually increase if intensive interaction with others does not happen in language setting because class interaction in the English learning process is vital factor to encourage students to use English language as means of communication; in other words language production will occur when interaction happens (Sundari, 2017).…”
Section: Introductionmentioning
confidence: 99%